2007
DOI: 10.1107/s0021889807005821
|View full text |Cite
|
Sign up to set email alerts
|

Biological solution scattering: recent achievements and future challenges

Abstract: In the post-genomic age it is apparent that as structures of larger macromolecules and their complexes are investigated, structure-function investigations are often confronted with the necessity to apply a portfolio of tools for biochemical and biophysical characterization. A survey of the published literature over the last decade reveals that publications in the area of structural biology employing neutron or X-ray scattering as one of their techniques tripled since 1995. Yet, taken as a whole, the contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Data from techniques such as electron microscopy, which produces images but not scattering curves, are also hard to compare. Finally, there have been recent efforts to combine low-resolution data, atomic resolution data and computer modeling to maximize the information gained from each technique (Grossmann, 2007;Suhre et al, 2006). Timeresolved reconstructions used in conjunction with these techniques will provide deeper insight into the changes that take place in a molecule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from techniques such as electron microscopy, which produces images but not scattering curves, are also hard to compare. Finally, there have been recent efforts to combine low-resolution data, atomic resolution data and computer modeling to maximize the information gained from each technique (Grossmann, 2007;Suhre et al, 2006). Timeresolved reconstructions used in conjunction with these techniques will provide deeper insight into the changes that take place in a molecule.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these ab initio algorithms allow users to propose molecular shapes without relying on previous knowledge. These reconstruction programs have produced shape envelopes for many proteins (Svergun & Koch, 2002;Grossmann, 2007) and nucleic acids (Nö llmann et al, 2004;Funari et al, 2000), enabling straightforward comparison between SAXS measurements and structural models.…”
Section: Introductionmentioning
confidence: 99%
“…79 X-ray solution scattering results can also usefully be combined with those of sedimentation and viscometry 80 as shown for the human pyruvate dehydrogenase complex 81 or for PEGylated antibody fragments. 82 SAXS results have been reviewed by various authors during the past two years [83][84][85][86] and descriptions of the most popular data analysis and modelling software are also available. 87 In the simplest applications the contribution of SAXS to structural studies lies in the verification of the similarity between the models and those obtained by crystallography, [88][89][90][91][92][93][94] nuclear magnetic resonance (NMR), as in the case of the Josephin domain of ataxin-3, 95 or homology modelling, as for the natural killer inhibitory receptor Irp60.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…Because membrane proteins and surfactant molecules have distinctly different electron densities, their complex formation makes the analysis of SANS or SAXS data extremely difficult. 11 Recently, Berthaud et al reported that, at adequate conditions, n-dodecyl-b-D-maltopyranoside molecules and aquaporins form an elliptical, toroid-shaped corona in an aqueous solution. The shape of the protein-surfactant complex was deduced from complementary results from size exclusion chromatography, SAXS, refractometry experiments and coarsegrained modelling.…”
Section: Introductionmentioning
confidence: 99%